Un progetto di edizione digitale del codice Napoli, Biblioteca Nazionale, MS XIII.B.29. - Omar Khalaf; Raffaele Cioffi (Umanistica Digitale, 2018)
This article presents a proof-of-concept for a digital edition of Napoli, Biblioteca Nazionale MS XIII.B.29. The value of this codex resides in being the only book containing late Middle English literature held in an Italian library. It contains a number of romances and a hagiographic poem that enjoyed widespread circulation in fourteenth- and fifteenth-century England, along with several yet unedited medical prescriptions. Apart from its philological and literary relevance – most of the texts contained may differ even remarkably from the rest of their traditions – the presence of notes in Italian, and, more importantly, of a drawing suggesting a connection with the Italian philosopher Tommaso Campanella demonstrate the historical importance of the manuscript. These marginalia may help contextualise the use of the codex in the cultural panorama of Naples in the sixteenth and seventeenth centuries. This project aims to provide a tool that can favour the study of a mostly unknown but unique codex, at the same time preserving its material integrity. Along with the strategies of text mark-up and the encoding of all the paratextual items, a preliminary design for an edition is illustrated, which will be produced using the EVT open source software.